Chinggis Khan, Women, and the West: Literary and Cinematic Remakes of the Secret History of the Mongols - Benedetta De Bonis (Humanities, 2024)
The name of Chinggis Khan and the women who contributed to the rise of his empire have long been associated with barbarism in the West. However, the rediscovery of the Secret History of the Mongols, a medieval Mongolian epic chronicle, in 1866, and its numerous translations circulating since the mid-20th century has led Western scholars to a total revaluation of these figures. This paper analyses the representation of Chinggis Khan and his queens in the literary and cinematic adaptations of the Secret History of the Mongols produced in Europe and the United States, specifically in English, French, and Italian. It critically engages with E. W. Said’s works, and with postcolonial and gender studies. The article argues that the portrayal of the Mongols has become increasingly positive in 20th and 21st century remakes of the epic chronicle, highlighting how the West reconsiders its relationship with cultural and gender otherness in an era marked by decolonisation and feminist claims.